SCHOOL-BASED ASSESSMENT IN THE CONTEXT OF SECONDARY SCHOOL PHYSICAL EDUCATION TEACHERS IN MALAYSIA - Veloo, Arsaythamby; Krishnasamy, Hariharan (PEOPLE: International Journal of Social Sciences, 2017)
The purpose of this study is to explore the implementation of School-Based Assessment among Physical Education teachers in Malaysian secondary schools. This study was based on the qualitative method using semi-structured interviews. For the purpose of this research, 16 (8 male and 8 female) Physical Education teachers were selected from 4 secondary schools located in Perlis, a state situated along the northern border of Malaysia. These schools are national schools which follow the national curriculum endorsed by the Malaysia Ministry of Education. Furthermore, the schools adopt the co-educational system. Based on the findings, the teachers mentioned that the administrators were not positioning the Physical Education (PE) subject as one of the main subjects in the school curriculum. The teachers have complained that not all of them are specialist teachers whereby most PE teachers in Malaysian secondary schools are not specialist teachers. Time allotment for a PE subject is two 40-minute lessons in a week. In the Malaysian education system, both teaching periods are shared by Physical Education and Health Education respectively. Furthermore, this subject is often debated because it seems to appear as a subject that needs to be taught in the curriculum without having a clear objective. Even though the objectives were already set by the Ministry, this subject remains unpopular because it is not included in the public examination. As a result, more measures need to be taken to ensure that the implementation of Physical Education subject can be of more benefit to the students